Experience feedback committee in emergency medicine: a tool for security management. Issue 11 (20th August 2013) - Lecoanet, André; Sellier, Elodie; Carpentier, Françoise; Maignan, Maxime; Seigneurin, Arnaud; François, Patrice
Abstract : Objective: Emergency departments are high-risk structures. The objective was to analyse the functioning of an experience feedback committee (EFC), a security management tool for the analysis of incidents in a medical department. Methods: We conducted a descriptive study based on the analysis of the written documents produced by the EFC between November 2009 and May 2012. We performed a double analysis of all incident reports, meeting minutes and analysis reports. Results: During the study period, there were 22 meetings attended by 15 professionals. 471 reported incidents were transmitted to the EFC. Most of them (95%) had no consequence for the patients. Only one reported incident led to the patient's death. 12 incidents were analysed thoroughly and the committee decided to set up 14 corrective actions, including eight guideline writing actions, two staff trainings, two resource materials provisions and two organisational changes. Conclusions: The staff took part actively in the EFC. Following the analysis of incidents, the EFC was able to set up actions at the departmental level. Thus, an EFC seems to be an appropriate security management tool for an emergency department.